Flexible robot manipulators modelling, simulation, and control - Tokhi, M. O.; Azad, A. K. M. (Abul K. M.) (The Institution of Engineering and Technology, 2008)
The book has 19 chapters and deals with the following subjects: single-link flexible manipulators; multi-link flexible manipulator; finite difference simulation; finite element simulation; symbolic manipulation; flexible space manipulators; open-loop control; enhanced PID control; force control; position control; collocated control; noncollocated control; decoupling control; soft computing approach; smart material flexible manipulators; rigid flexible manipulators and SCEFMAS.